Континентален и аналитички Платон – изгубени во интерпретацијата - Наумоска, Јасмина (Филозофски факултет, Скопје, 2013)
The analytic/continental divide in the field of ancient philosophy, especially in Plato studies, has been reduced to the dichotomy argument/context. Underlining the argumentative aspect of the text, the analytic tradition was claimed to be "anachronistic" in reading contemporary meanings in the ancient texts where no such meanings are present. The continental tradition, highlighting the contextual elements of the life dimension of human existence and giving emphasis on the literary form of the texts, was accused of "historicism" and of weak argumentation which resulted in no philosophical progress. This text summarizes the specific interpretations of these two philosophical traditions in Plato studies, namely Vlastos' analytic interpretation on one side, and the continental interpretations of Derrida, Irigaray, Cavarero and Gadamer, on the other. At the same time, this text points out certain discussions in the last several decades within the two traditions (Annas, Cooper, Gadamer, Davidson) that diverge in the direction towards one another. This divergence indicates that the already established parameters in interpreting Plato's dialogues give limited interpretative space. In the analytic circles the unitarian perspectives and contextualization of the argumentation are seriously considered, while in the continental, there are certain requirements for language analysis. With the classic XIX century's translations, Plato stopped being lost in translation, but now, as never before, his philosophy is lost in interpretation. This is a result of the mutual miscommunication between the divided schools, following the inheritance of the philosophical traditions.